Studies on factors affecting reproductive performance and mortality of Small East African goats and their crosses - Mtenga, L.A.; Kifaro, G.C.; Belay, B. (1992)
This study compares genetic and non-genetic factors affecting the reproductive performance and mortality rates of Kamorai x Small East African (SEA), Boer x SEA and SEA goats using records kept at the Department of Animal Science and Production, Sokoine University of Agriculture, Tanzania, between 1972 and 1989.Age at first kidding and kidding interval ranged from 638 to 984 days and 293 to 419 days, respectively. Age at first kidding was significantly (P<0.001) influenced by period of kidding. Period of kidding and season of previous kidding affected kidding interval significantly (P<0.01 and P<0.05, respectively).Overall average mortality rate was 40.6% and 25.7% for preweaning and postweaning periods, respectively. Animals with birth weights of less than 1.5 kg had the highest preweaning mortality rate (57.9%). The lowest preweaning mortality rate occurred in animals with a birth weight of greater than 2.6 kg (29.8 %). Twins exhibited a higher preweaning mortality rate than singles (48.3% vs 38.5%). Preweaning mortality was lower in period I (1972-1974) than in later years.Non-genetic factors, especially period and season of kidding, were the main sources of variation in reproductive performance and mortality rate. Crossing SEA goats with Kamorai and Boer showed little improvement in these factors. Poor feeding management and disease control probably prevented the crosses from expressing their genetic potential.